Study of the difference in coverage of the Israeli operation in Gaza (December, 2008 to January, 2009) in the New York Times and BBC - Dagher, Nader (My University, 2010)
Coverage of the Middle East by western media is often an issue of argument. The most controversial is how this media cover the Israeli-Palestinian conflict. While media defend itself by claiming the balanced, objective coverage, and being equally distanced from both sides, it is criticized by both the pro Palestinian and pro Israeli audiences for being sympathetic with one side or the other, like the idea of being a part of a western unfairness to the Middle Eastern conflict (Said, 1997, Fish, 2004) This study is a textual analysis of New York Times and British Broadcasting Corporation (BBC) coverage of war Israel initiated in Gaza between December 27th, 2008 and January 17th, 2009. These two western media can be seen as different organizations in their structure, relation with the governments, and editorial policies. Stories published in their electronic version www.bbc.co.uk and www.nytimes.com were analyzed by applying Merrill?s (1968) model to the sources used in this coverage, and information quoted from these sources. Analysis included five categories: sources, specificity in naming these sources, and specificity in reporting casualties when reported by such sources. The analysis found differences in the use of sources between these two western media in covering the Israeli-Palestinian conflict, but maintaining that both NYT and BBC tend to use Israeli more than Palestinian sources, with NYT heavily relying on more Israeli sources, and BBC using closer to an equal number of sources from both sides. Results of in inequality of number of sources used by media can also relate to the differences in which the Israel and the Palestinians have dealt with the media, and the availability of personnel and information on both sides, which can make an excuse for media to use sources of one side more than the other.
This file was last viewed in Adobe Reader 10.1.0
Keywords: Gaza War, 2008-2009--Press coverage; Gaza Strip--Press coverage; Israel--Press coverage; Arab-Israeli conflict--Press coverage; Press--United States; Press--Great Britain; Broadcast journalism--Great Britain; Journalism--Objectivity--United States; Journalism--Objectivity--Great Britain; New York Times Company; British Broadcasting Corporation